2015
DOI: 10.1155/2015/201843
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Systemic Oxidative Stress Profiles in COPD: A Potential Role of Gender

Abstract: Oxidative stress (OS) plays a key role in the muscle impairment and exercise capacity of COPD patients. However, the literature reveals that systemic OS markers show great heterogeneity, which may hinder the prescription of effective antioxidant supplementation. This study therefore aimed to identify OS markers imbalance of COPD patients, relative to validated normal reference values, and to investigate the possibility of systemic OS profiles. We measured systemic enzymatic/nonenzymatic antioxidant and lipid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 47 publications
3
31
0
Order By: Relevance
“…To a lesser extent than MDA, other biomarkers of lipid peroxidation have been studied in plasma of COPD patients of which have been described increased levels compared to controls (Table 1): lipid peroxides, determined spectrophotometrically either using their ability to convert iodide to iodine in a solution containing cholesterol-iodide [59] or following their reaction with peroxidase and a subsequent color production [62]; conjugated dienes, that are formed in the process of lipid peroxidation as a result of a reconfiguration of double bonds and yield a characteristic absorbance peak [27, 59]; oxidized LDL, determined spectrophotometrically with a competitive enzyme-linked immunosorbent assay (ELISA) kit [62] and 8-isoprostane, assayed with a specific enzyme immunoassay kit [63]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To a lesser extent than MDA, other biomarkers of lipid peroxidation have been studied in plasma of COPD patients of which have been described increased levels compared to controls (Table 1): lipid peroxides, determined spectrophotometrically either using their ability to convert iodide to iodine in a solution containing cholesterol-iodide [59] or following their reaction with peroxidase and a subsequent color production [62]; conjugated dienes, that are formed in the process of lipid peroxidation as a result of a reconfiguration of double bonds and yield a characteristic absorbance peak [27, 59]; oxidized LDL, determined spectrophotometrically with a competitive enzyme-linked immunosorbent assay (ELISA) kit [62] and 8-isoprostane, assayed with a specific enzyme immunoassay kit [63]. …”
Section: Introductionmentioning
confidence: 99%
“…A decreased level of vitamin C [25, 28, 62] and E [25, 28, 30], as well as no difference in the levels of vitamin A [27], C [40, 48, 95] and E [27] has been described in COPD compared to healthy controls. No differences have also been found in the different stages of severity of disease [96].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maury et al found increased lipid peroxidation and copper levels combined with decreased levels of GSH, and Glutathione peroxidase (Gpx) activity suggesting an antagonist relationship between Cu and Zn. They claim that higher Cu levels are a result of increased lipid peroxidation, whereas decreased Zn levels are due to consumption of Zn by antioxidant mechanisms which are trying to prevent oxidant damage [8].…”
Section: Discussionmentioning
confidence: 99%
“…In COPD, excessive amounts of free radicals and reactive oxygen metabolites are produced as a result of impaired inflammatory response due to progressive airway obstruction. Oxidant molecules react with proteins, lipids and nucleic acids, leading to cell dysfunction or death [8].…”
Section: Introductionmentioning
confidence: 99%